HYDRAULIC HERITAGE: QANATS AND LANDSCAPE DYNAMICS IN THE LIBERATED KARABAKH TERRITORIES (Journal of Geography and Environmental Management, 2026)
Qanat systems are traditional underground channels designed for water transportation and play a vital role in providing reliable water sources for both drinking and irrigation purposes. Over the past two years, monitoring was conducted in the territories of Karabakh liberated from occupation to assess the condition of qanats after a 30-year period. The findings revealed that many qanats still show traces of past military activities. A comprehensive study was undertaken to evaluate the technical condition and restoration potential of the qanats. In parallel, land reclamation, hydrogeological, and agro-soil investigations were carried out across the  entire qanat distribution area. The results indicated that conditions varied significantly among the Agdam, Fuzuli, and Jabrayil districts. Recommendations include regular monitoring of water and soil quality, implementation of effective qanat rehabilitation methods, and the optimal utilization of qanat water for both domestic and agricultural purposes. This study emphasizes the importance of qanat systems for arid and semi-arid regions and offers practical recommendations for the sustainable management of water and land resources, to enhance the socio-economic well-being of local communities.
Keywords: Qanat; Irrigation; Hydraulic structure; Degradation; Restoration